The Double Burden of Work and Life and Turnover Intention Among Migrant Garment Workers: A Case Study From an Industrial Zone in Vietnam - Pham, Cong Tuan; Phung, Dung; Nguyen, Thi Lien Huong; Nguyen, Thi Vinh; Chu, Cordia (Journal of Population and Social Studies [JPSS], 2023)
This study aims to determine the prevalence and associated factors of turnover intention among interprovincial migrant workers in garment companies in a rapidly urbanizing area of Vietnam. This study employed a mixed method approach, beginning with in-depth interviews with 12 migrant garment workers to develop survey instruments, which were then used in a quantitative survey. The survey recruited and interviewed 328 inter-provincial migrant workers working in garment factories using a social mapping sampling method. Multivariable backward stepwise logistic regression analysis was used to investigate factors associated with worker turnover intention. The results show a high prevalence of turnover intention (46.3%) among the survey participants. High psychological demand (OR = 2.5, 95% CI [1.4, 4.4], p < .001), low job control, income dissatisfaction (OR = 3, 95% CI [1.5, 6], p < .01), migration intention (OR = 13, 95% CI [7, 24], p < .001) and male gender (OR = 2.5, 95% CI [1.3, 4.8], p < .01) are factors significantly associated with turnover intention among migrant workers. This study provides a model for understanding migrant laborers’ turnover intentions in the garment industry, as well as critical data for developing needs-based intervention programs for this vulnerable group, such as appropriate resettlement strategies and the creation of a healthy working environment, both of which could play essential roles in the garment industry’s workforce retention.